THE IMPACT OF TASK-BASED LANGUAGE TEACHING (TBLT) IMPLEMENTATION ON STUDENTS’ ENGLISH LEARNING MOTIVATION: INDONESIAN SENIOR HIGH SCHOOL VIEWS - Zakiya Mumtaza; Mobit; Bagas Sulistyo (Esteem Journal of English Education Study Programme, 2025)
This research investigates the implementation of Task-Based Language Teaching (TBLT) in an English classroom at an Indonesian senior high school, with a specific focus on students’ perceptions of its influence on their motivation to learn English. Adopting a qualitative case study approach, the study gathered data through classroom observations, semi-structured interviews, and document analysis. Thematic analysis, guided by Braun and Clarke’s six-phase framework, was used to identify key themes across diverse data sources. The results revealed that TBLT was enacted through clearly delineated stages pre-task, task, and post-task and was characterized by structured planning and dynamic classroom engagement. Students expressed enhanced motivation, confidence, and involvement, particularly when the tasks reflected their personal experiences and were reinforced through constructive teacher feedback and peer collaboration. These findings offer valuable implications for EFL educators, curriculum planners, and researchers interested in learner-centered pedagogy and motivational practices in secondary education. Departing from the predominant focus on linguistic proficiency, this study emphasizes the affective dimensions of TBLT, shedding light on how carefully designed, contextually relevant, and interaction-rich tasks can nurture student motivation by promoting autonomy, personal relevance, and cooperative learning.